Exploring EFL Student’s Reading Comprehension of Narrative Text Through Listen-Read-Discuss (LRD) Strategy: A Case Study At Second Grade of SMK PGRI Lemahabang - Ibnurosita Augustia Ningtyas; Yogi Setia Samsi; Iwan Ridwan (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study is to determine the use of Listen Read Discuss (LRD)strategies to improve students' reading comprehension of narrative texts in class eleven of Vacational High School. There are several problems in this research. First, the shortage of students vocabulary. Second, students are less motivated to read. Third, students are hard to get Main ideas in reading comprehension. The population of this research is 23 students. That Data collection techniques in this study using observation and interviews. The research sample is class XI TKJas an interview class consisting of 5-10 students, and the remaining number of students is used for observation. Collecting data by providing interview questions which are given differently. The results obtained in this study are that students are taught step by step so that it can be concluded that the Listen Read Discuss (LRD) strategy is effective in improving students' reading skillsunderstanding of narrative text in class XI Vacational High School TKJ